INVENTORY OF DIVERSITY OF PATHOGENIC FUNGI OF POTATO TUBER (Solanum tuberosum L.) SEEDS IN TRADITIONAL STORAGE WAREHOUSES ON LOMBOK ISLAND - Musafir; Kadafi, Muamar; Nursamsidar (Universitas Veteran Bangun Nusantara, 2025)
Post-harvest diseases caused by pathogenic fungi are one of the real threats to the availability and quality of potato seedlings and tubers (Solanum tuberosum L.), especially in traditional warehouse storage and guidance systems. This descriptive research was carried out using a survey method with the aim of inventorying the diversity of disease-causing fungi, as well as measuring the intensity of infection in potato tuber seedlings in two traditional storage warehouse locations, on Lombok Island. The research series will be carried out from October 2023 to January 2024. Sampling was carried out by purposive sampling. The results of the study showed that the average value of disease intensity in potato tuber seedlings in the traditional storage warehouse of Setiling Village reached 19.29%, while in the warehouse of Santong Village reached 17.79%. The results of the identification of pathogenic fungi revealed that there were differences in the distribution of species based on storage locations. In potato tuber seedlings in the nursery warehouse of Setiling Village, a species of fungus Fusarium sp. and Phytophthora infestans., while in the nursery warehouse of Santong Village, the results of the identification of Rhizoctonia sp. and Fusarium sp. The characteristics of the storage environment are also noted: the average temperature in the warehouse in Setiling ranges from 22–29ºC with a humidity of 80–99%, and in Santong Village, the temperature is 24–30ºC with a humidity of 78–92%. The results of this study indicate that the environmental conditions in both warehouses have the potential to support the development of certain pathogens. Keywords: Inventory, Patato Seed Bulbs, Pathogenic Fungus